Solving MHD Flow over a Shrinking Wedges Using Shooting Technique - Akiruddin, Nur Hazimah; Aman, Fazlina (Enhanced Knowledge in Sciences and Technology, 2023)
The study investigates solving MHD flow over a stretching and shrinking wedges using shooting technique. A similarity transformation was used to transform from partial differential equations governing the flow and heat transfer into a system of ordinary differential equations. These equations are then solved numerically using shooting technique with the Runge-Kutta Fehlberg method in Maple software. The issue will be quantitatively addressed in this study, and the findings will be compared to those obtained in [1]. For the shrinking case, the existence of the solution depends on the shrinking strength λ and the angle of the wedge Ω. The range of λ (for which the solution exists) increases as the angle of the wedge Ω increases